Atomic scale growth dynamics of nanocrystals within carbon nanotubes - Warner, J; Plant, SR; Young, N; Porfyrakis, K; Kirkland, A; Briggs, G (2011)
The confined interior region of carbon nanotubes has proved to be an effective "nano-test-tube" to conduct chemical reactions in a restricted volume. It also benefits from being thin and relatively transparent to electrons, enabling structural characterization using high-resolution transmission electron microscopy. This permits real-time monitoring of chemical reactions with atomic resolution. Here, we have studied the dynamics of single Pr atoms released from Pr2@C72 metallofullerenes. We show that the Pr atoms form small nanoclusters that subsequently coalesce to ordered, stable nanocrystals within the confines of a carbon nanotube. This process has been tracked in situ with atomic-resolution using low-voltage aberration-corrected high-resolution transmission electron microscopy. We reveal that nanocrystal formation within a nanotube does not generally occur by the addition of single atoms to one pre-existing cluster but rather through aggregation of several smaller clusters. These results provide some of the deepest insights into the dynamics of single-atom behavior in the solid state. © 2011 American Chemical Society.